(untitled) (Texas Journal of Engineering and Technology, 2023)
The amount of moisture a mineral can absorb depends on the shape, size, and location of the capillaries, as well as the water’s affinity for the mineral. The different binding of moisture to the mineral matter affects its physical characteristics in different ways, and it is difficult to determine this binding. Therefore, measuring the moisture content of solid and dispersible mineral substances is difficult and leads to inadequate graded characteristics.